Case‐finding in primary care for coeliac disease: Accuracy and cost‐effectiveness of a rapid point‐of‐care test. Issue 6 (1st July 2018) - Esteve, Maria; Rosinach, Mercè; Llordés, Montserrat; Calpe, Judit; Montserrat, Glòria; Pujals, Mar; Cela, Abel; Carrasco, Anna; Ibarra, Montserrat; Ruiz-Ramirez, Pablo; Tristán, Eva; Arau, Beatriz; et al.
Abstract : Background: An on‐site, rapid, fingertip, whole‐blood point‐of‐care test (POCT) is attractive for active case‐finding of coeliac disease (CD) in primary care because of its simplicity. Aim: The aim of this article is to assess the usefulness and cost‐effectiveness of adult case‐finding using a POCT based on deamidated gliadin peptide antibodies (IgA/IgG‐DGP) in primary care for CD diagnosis. Methods: A case‐finding study for CD was conducted by using an easy‐to‐use, on‐site, whole‐blood for IgA/IgG‐DGP‐based fingertip POCT compared with tTG2 in 350 individuals. Sample size was calculated based on 0.28% prevalence in the reference population. Duodenal biopsies for histology, intraepithelial lymphocytes and in situ deposition of tTG2 were obtained if tTG2 and/or POCT were positive. Accuracy and cost‐effectiveness of strategies using serology or POCT were calculated. Results: Prevalence of CD was 1.14% (95% CI, 0.3–3.4), almost double what was previously observed. Four patients were diagnosed with CD. tTG2 was positive in three (0.85%) and POCT in 29 (8.2%). Sensitivity of POCT for CD was 100%, specificity 93%, PPV 14%, and NPV 100%. POCT followed by duodenal biopsy was the most cost‐effective approach in our setting (standard diagnosis: €13, 033/case; POCT + duodenal biopsy: €7360/case). Conclusions: A negative POCT allows ruling out CD in primary care, making it suitable for case‐finding. POCT strategy was the most cost effective.